Bullet Embolization: Multidisciplinary Approach by Interventional Radiology and Surgery - Nolan, Timothy; Phan, Ho; Hardy, Andrew Hal; Khanna, Pavan; Dong, Paul (Seminars in Interventional Radiology, 2012)
Bullet embolization after penetrating trauma is an infrequent but important phenomenon. It presents an unexpected sequelae to the otherwise predictable injury pattern of penetrating missile injury mechanism and poses a challenging diagnostic and therapeutic dilemma. Bullets from penetrating wounds can gain access to the vasculature and migrate to nearly every large vascular bed. Patients can be asymptomatic, but the potential complications can be devastating including limb-threatening ischemia, sepsis, endocarditis, cardiac valvular incompetence, pulmonary embolism, stroke, and even death. The exact incidence of bullet embolization is unknown, but it was estimated to be 0.3% during the Vietnam War and 1.1% in the recent conflict in Afghanistan and Iraq. The scarcity of the condition and the lack of concentrated experience at any single institution contribute to the controversies pertaining to the management approach. Traditionally, surgical extraction of embolized bullets may involve difficult and invasive surgical exposures. Recent advancement in endovascular techniques provides an additional option in this treatment algorithm. In this article, we describe a case of venous bullet embolization from the left iliac vein treated by a combined endovascular and surgical approach.
Keywords: penetrating trauma; bullet embolization; endovascular retrieval; interventional radiology